Hydrocracking of N - Heptane with a NiO - MOOY Zeolite as catalyst . The Network of Reaction - Shahrazad Raouf; Mazin Abdul - Zahra (Engineering and Technology Journal, 2005)
Abstract The hydrocracking of n - heptane has been carried out in a fixed bed reactor at 20 bar pressure and with Hyn - heptane molar ratio of 5 using 4wt % NiO - 8wt % MoO Y zeolite as a catalyst . The W / Fo ratio was varied between 5-30kg.h./kmol at different reaction temperature 325 , 350 , 375 , 400 and 425 ° C . The product was analyzed by gas chromatography . The following activity order was obtained : HY > CuY > CrHY > CrY > MnY . All forms of Zeolites ( HY , CuY , CrHY , CrY , and MnY ) were prepared from mono valent cationic sodium type by means of ion exchange process . This modification was carried out to improve the catalytic properties of NiO - MoO Y zeolite catalyst . The ion exchange with Cr , Mn , Cu and CrH , were resulted the lowest rate comparing with NH .. The reaction temperature influenced the activity of NiO - MoO / Y zeolite catalyst . The isomerization of n - heptane attains a maximum at 375 ° C , it drops sharply at higher temperatures . In addition the NiO - MoO / CrHY catalyst has good activity toward isomerization compared with other types of catalysts . The kinetics of the reaction has been studied using the conversion and yield values explorated at time on stream to zero . The experimental data were fit well by a pseudo - first order kinetic equation and the kinetic constant values obtained . The kinetic parameters of the 2 - methyl hexane and 3 - methyl hexane have been obtained from the initial selectivities .